NGA- A Novel Hypothetical Drug Model: Combinatorial Approach to Multifactorial Alzheimer’s Disease - Devi, C. S.; Mohanasrinivasan, V.; Priyadoss, C. George; Arora, Nikhil; Singh, Bharti; Mittal, Neetu; Agarwal, Shubham; Saxena, Shwetank (Current Drug Discovery Technologies, 2015)
Alzheimer’s disease (AD) is supposed to stanch from inappropriate waving in the brain sections related to memory and perception. The incidence of AD in distressed person associated with an upsurge in the accumulation of amyloid plaque-rich senile plaques and neurofibrillary tangles in the brain. We hypothesize that a combination therapy provides a new treatment for AD. We propose that an anti-AD drug, NGA, a combination of NSAIDS, Galanthamine and ACS-40 may be useful in preventing the formation of amyloid plaques from β-amyloid. Being a widespread incurable disease, the treatment for Alzheimer’s has been at the forefront of the medical research work. We propose a novel drug-like NGA will allow for the effective control and treatment of the progression of AD by preventing acetylcholinesterase activity and reducing plaque formation that forms the distinctive symptom for the identification of the onset of AD. A combinatory use of NSAID with a natural neurotransmitter will allow for an efficient control of amyloid beta toxicity and will open doors for the treatment of a myriad of other neurodegenerative diseases.
Keywords: galanthamine